Identification of the oil palm bagworm, Mahasena corbetti tams (Lepidoptera: Psychidae) via molecular techniques and its biocontrol assay using Bacillus thuringiensis - Thakib Maidin, Mohd Shawal; Mohd Hashim, Amalia; Kamarudin, Noorhazwani; Ahmad, Siti Nurulhidayah; Mohd. Masri, Mohamed Mazmira; Abdul Rahim, Raha; Jamian, Syari (Malaysian Palm Oil Board, 2023)
The larvae of the bagworm Mahasena corbetti Tams (Lepidoptera: Psychidae) cause significant yield losses by defoliation of the oil palm crop in Malaysia. This necessitates the development of an effective and sustainable control strategies against this pest. The objective of this study was to identify M. corbetti via molecular techniques and evaluate the potential of a local strain of Bacillus thuringiensis (MPOB Bt1), as a biocontrol agent for the pest. Morphological and molecular analysis was performed to identify M. corbetti, using the mitochondrial cytochrome oxidase I (COI) gene for genetic identification. The results showed that M. corbetti isolate SH01 (GenBank accession number MN373269) had a high degree of similarity (98.52%, 0.0 E-value) with the COI gene of M. corbetti voucher GB270DN1795 (GenBank accession number MG574312) collected in India and 100% BOLD similarities with the COI gene of M. corbetti from Singapore (BOLD ID PSYCH113-12). Laboratory bioassay showed 100% mortality of M. corbetti larvae three days after treatment with MPOB Bt1 (108 spores/mL). The results demonstrate the potential of MPOB Bt1 as an environmentally friendly biopesticide against M. corbetti in oil palm, but optimisation and efficacy in other pests require further research. Furthermore, biocontrol can be used as part of an integrated pest management program against bagworms and other lepidopteran pests.